2018
DOI: 10.7717/peerj.5581
|View full text |Cite
|
Sign up to set email alerts
|

Distribution ofPorphyromonas gingivalis fimAandmfa1fimbrial genotypes in subgingival plaques

Abstract: BackgroundStrains of periodontal disease-associated bacterium Porphyromonas gingivalis have different pathogenicity, which can be attributed to clonal genetic diversity. P. gingivalis typically expresses two types of fimbriae, FimA and Mfa1, which comprise six (I, Ib, II, III, IV, and V) and two (mfa53 and mfa70) genotypes, respectively. This study was conducted to investigate the distribution of the two fimbrial genotypes of P. gingivalis in clinical specimens.MethodsSubgingival plaques were collected from 10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 51 publications
0
13
1
Order By: Relevance
“…Type 70 seemed a major mfa1 genotype for P. gingivalis , whereas most P. gulae strains had type 53 ( Figure 4 ). In a previous study, the relationship between the fimA and mfa genotypes was weakly observed in P. gingivalis , such as type II strains harboring type 70 mfa1 rather than type 53, and mfa1 was absent in the type V strains [ 13 ]. These previous findings were consistent with our observation that most of type II strains were type 70 in the mfa1 genotypes, but were not consistent with the presence of mfa1 in P. gingivalis strains with type V fimA .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Type 70 seemed a major mfa1 genotype for P. gingivalis , whereas most P. gulae strains had type 53 ( Figure 4 ). In a previous study, the relationship between the fimA and mfa genotypes was weakly observed in P. gingivalis , such as type II strains harboring type 70 mfa1 rather than type 53, and mfa1 was absent in the type V strains [ 13 ]. These previous findings were consistent with our observation that most of type II strains were type 70 in the mfa1 genotypes, but were not consistent with the presence of mfa1 in P. gingivalis strains with type V fimA .…”
Section: Discussionmentioning
confidence: 99%
“…Fimbriae of P. gingivalis are the virulence factor for adhering to a host cell and tissue as the first step of colonization [ 6 ]. In P. gingivalis , fimbriae are classified as FimA fimbriae and Mfa1 fimbriae [ 13 ]. FimA is assembled into the polymer with the expression of accessory proteins FimBCDE [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…The detection rate of Porphyromonas gingivalis , one of the major pathogens of periodontitis in subgingival biofilm, is as high as 60.9% ( Nagano et al, 2018 ). In recent years, it has been found that Candida albicans , a pathogen of denture stomatitis, also has an increased frequency of subgingival separation in patients with periodontitis ( McManus et al, 2012 ; Sardi et al, 2012 ; Marsh and Zaura, 2017 ).…”
Section: Introductionmentioning
confidence: 99%
“…It is particularly relevant to highlight that in ruminant animals the chemical and microbial content of the rumen interacts with the oral counterparts (Myer et al 2015). Among the microbial adhesins, the role played by fimbriae and other appendicular structures deserves attention (Marsh et al 2011), especially among the main periodontal pathogens, such as the genus Porphyromonas (Socransky & Haffajee 2005, Nagano et al 2018.…”
Section: Discussionmentioning
confidence: 99%